Sadness regulation strategies and measurement: A scoping review. - Sumaia Mohammed Zaid; Fonny Dameaty Hutagalung; Harris Shah Bin Abd Hamid; Sahar Mohammed Taresh (PLoS ONE)
Backgrounds Accurate measurement and suitable strategies facilitate people regulate their sadness in an effective manner. Regulating or mitigating negative emotions, particularly sadness, is crucial mainly because constant negative emotions may lead to psychological disorders, such as depression and anxiety. This paper presents an overview of sadness regulation strategies and related measurement. Method Upon adhering to five-step scoping review, this study combed through articles that looked into sadness regulation retrieved from eight databases. Results As a result of reviewing 40 selected articles, 110 strategies were identified to regulate emotions, particularly sadness. Some of the most commonly reported strategies include expressive suppression, cognitive reappraisal, distraction, seeking social or emotional support, and rumination. The four types of measures emerged from the review are self-reported, informant report (parents or peers), open-ended questions, and emotion regulation instructions. Notably, most studies had tested psychometric properties using Cronbach's alpha alone, while only a handful had assessed validity (construct and factorial validity) and reliability (Cronbach's alpha or test-retest) based on responses captured from questionnaire survey. Conclusion Several sadness regulation strategies appeared to vary based on gender, age, and use of strategy. Despite the general measurement of emotion regulation, only one measure was developed to measure sadness regulation exclusively for children. Future studies may develop a comprehensive battery of measures to assess sadness regulation using multi-component method.